Enhanced Photocatalytic Activity of Hierarchical Macro-Mesoporous Anatase by ZrO2 Incorporation - M. L. García-Benjume; M. I. Espitia-Cabrera; M. E. Contreras-García (International Journal of Photoenergy)
The effect of the addition of zirconia in the photocatalytic behaviour of titania is analysed. In order to increase the ways for reagent and product diffusion in the material, a sol-gel hydrothermal synthesis route using Tween-20 as a directing agent to obtain a hierarchical macro-mesoporous structure is proposed. Nanostructured macro-mesoporous TiO2/ZrO2 photocatalyst with 0, 10, 20, 30, and 100% mol of ZrO2 were obtained and calcined at different temperatures. The crystalline structure was analyzed by X-ray diffraction and TEM. The porosity was confirmed by SEM, TEM, and nitrogen adsorption-desorption isotherms. The worm-like mesoporous structure was confirmed by TEM. The specific surface areas obtained by Brunauer-Emmet-Teller method (BET) ranged from 125 to 180 m2/g. The Tween-20 total elimination from the structure by thermal treatment was confirmed by infrared spectroscopy and thermogravimetric analysis. Additionally, the photocatalytic effect of the zirconia addition was studied in the methylene blue (MB) degradation reaction, and the best photocatalytic activity was obtained in the sample with 10% mol of ZrO2, degrading up to 92% the MB.